2008
DOI: 10.1001/jama.299.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Suppression and Radiation vs Radiation Alone for Prostate Cancer

Abstract: EVERAL RANDOMIZED STUDIES [1][2][3][4][5] have documented a prolongation in overall survival, prostate cancer-specific survival, or both when androgen suppression therapy (AST) is combined with external beam radiation therapy (RT) compared with RT alone in the management of unfavorable localized and locally advanced prostate cancer. Therefore, in men with these stages of disease, RT and AST have become a standard of care.However, evidence from pooled analyses of randomized studies 6 as well as large patient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
428
0
24

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 594 publications
(467 citation statements)
references
References 30 publications
15
428
0
24
Order By: Relevance
“…It has recently been shown in a randomized trial that even though complete androgen blockade adjuvant to RT compared with RT alone resulted in a mortality benefit, this was not true for subgroups with moderate or severe comorbidity. 33 Such identification of patients for whom side effects from adjuvant treatment outweigh the antitumour effects is important in order to individualize therapy. In our opinion, precautions should be made until the possible relation between AAs and cardiovascular morbidity is clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown in a randomized trial that even though complete androgen blockade adjuvant to RT compared with RT alone resulted in a mortality benefit, this was not true for subgroups with moderate or severe comorbidity. 33 Such identification of patients for whom side effects from adjuvant treatment outweigh the antitumour effects is important in order to individualize therapy. In our opinion, precautions should be made until the possible relation between AAs and cardiovascular morbidity is clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only in select cases ADT is given as primary treatment for localised prostate cancer. In conjunction with external beam radiation therapy, 2 years of androgen deprivation is clearly advantageous [11]. In patients with positive lymph nodes following radical prostatectomy, addition of androgen deprivation improves survival [12].…”
Section: Androgen Deprivation Therapymentioning
confidence: 99%
“…Because an increase in ACM was noted only for men aged >73 years, in whom increased comorbid illness would be expected compared with men aged <73 years, it is likely that the interaction noted in a postrandomization analysis between ADT and the Adult Comorbidity Evaluation-27 comorbidity score, in which men with moderate to severe comorbidity did not benefit in terms of overall survival for the addition of ADT to radiotherapy, also may explain the current results. 13 Specifically, ADT may accentuate underlying comorbidity, which probably is cardiovascular based on previous reports. [2][3][4]13 Finally, prior randomized studies have demonstrated an overall and/or cancer-specific survival benefit with the addition of hormone therapy to external-beam radiation in men with high-risk disease.…”
mentioning
confidence: 95%
“…13 Specifically, ADT may accentuate underlying comorbidity, which probably is cardiovascular based on previous reports. [2][3][4]13 Finally, prior randomized studies have demonstrated an overall and/or cancer-specific survival benefit with the addition of hormone therapy to external-beam radiation in men with high-risk disease. [13][14][15][16][17] In the current study, 12% of patients had high-risk disease; however, hormone therapy was used in conjunction with brachytherapy, and a survival benefit has not been demonstrated with the addition of hormone therapy in that setting.…”
mentioning
confidence: 95%
See 1 more Smart Citation